HELLP syndrome in height - Tapia, Carmen (2015)
OBJECTIVE: To study the incidence and management of HELLP Syndrome at high altitude. DESIGN.- Descriptive, retrospective, analytical study. RESULTS: From 10 cases hospitalized in ICU for preeclampsia or severe eclampsia, 4 fulfilled criteria for HELLP syndrome, with mean age 33,6, parity 4,6, pre natal control in only 40%. Mean blood pressure was 114,6 mmHg, gestational age 29 weeks, all bad anasarca, echymosis, jaundice, oliguria or anuria. Management was in charge of ICU. One patient died (20%) and perinatal mortality was 100%. CONCLUSION: Early diagnosis, adequate prenatal control and treatment are essential to decrease HELLP syndrome's mobidity and mortality.